2014
DOI: 10.1242/jcs.146225
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast nucleolar protein Dnt1 regulates G2/M transition and cytokinesis by downregulating Wee1 kinase

Abstract: There was an error published in J. Cell Sci. 126, 4995-5004.One source of funding was accidentally omitted. The correct funding section is as shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Furthermore, our results are in line with yeast studies, in which Wee1 has a function beyond mitotic entry. Experiments with S. pombe showed that Wee1 regulation is part of the septation initiation network (SIN) during mitotic exit (45). In addition, the S. cervisiae Wee1 ortholog Swe1 constitutes an anaphase checkpoint, which controls proper activation of the APC/C to allow mitotic exit (46).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results are in line with yeast studies, in which Wee1 has a function beyond mitotic entry. Experiments with S. pombe showed that Wee1 regulation is part of the septation initiation network (SIN) during mitotic exit (45). In addition, the S. cervisiae Wee1 ortholog Swe1 constitutes an anaphase checkpoint, which controls proper activation of the APC/C to allow mitotic exit (46).…”
Section: Discussionmentioning
confidence: 99%
“…The coding sequence of firefly luciferase was PCR amplified using two sets of primers (#1305-1308, Table S3) and plasmid pFA6a-Firefly-luciferasekanMX6 (Yu et al, 2013) as template. Linear complementary backbone of pJK148-P nmt -GBP-mCherry(N) (where P nmt is P nmt81 , P nmt41 or P nmt1 ) or pUC119-P adh -GBP-mCherry(N)-hphMX6-lys1* (where P adh is P adh81 , P adh21 , P adh11 or P adh1 ) was also produced in two parallel PCRs using two sets of non-tailed or tailed primers (#1206, #1207, #1210, #1211, and #1321-1324; Table S3).…”
Section: Construction Of Strains Carrying Gbp-mcherry-fluc and Alp4-mentioning
confidence: 99%
“…In order to construct genomically tagged Alp4-R.luciferase, which can be used as an internal control for luciferase activity measurement, pFA6a-Renilla-luciferase-natMX6 (Yu et al, 2013) was used to add a C-terminal Renilla luciferase tag to the endogenous alp4 + locus to create the Alp4-R. luciferase (nat R ) allele using PCR-based gene targeting (Bahler et al, 1998).…”
Section: Construction Of Strains Carrying Gbp-mcherry-fluc and Alp4-mentioning
confidence: 99%
See 2 more Smart Citations